Several factors affect the audit quality in South Sulawesi Inspectorate - Muhammad Su’un; Usman Usman (Atestasi : Jurnal Ilmiah Akuntansi, 2021)
This study aims to assess the quality of audit results at the South Sulawesi Province Inspectorate Office. The competence, independence, objectivity, and integrity of auditors are the independent variables in this study, while the quality of audit results is the dependent variable. Purposive sampling was used as the method of sampling. Multiple Regression Analysis was used to analyze the data, which was then processed using SPSS 24. A questionnaire was distributed directly to the South Sulawesi Provincial Government Internal Supervisory Apparatus to collect data. The study found that auditor competence, independence, objectivity, and integrity have a significant positive effect on the quality of audit results, both simultaneously and partially. To improve audit quality, auditors must constantly monitor and improve the quality of their experience and knowledge at all levels of the Public Accounting Firm's organizational structure, including junior, senior, and higher levels, by attending training on relevant topics. Auditors are also expected to maintain an independent mental attitude, objectivity and integrity at all times.